So, you want to be a coder? : the ultimate guide to a career in programming, video game creation, robotics, and more! - Bedell, J. M. (Jane M.) (Be what you want series., 2016)
"So, You Want to Be a Coder? debugs the secrets behind a career in the diverse and state-of-the-art industry of working with computer code. In addition to tips and interviews from professionals in the industry, So, You Want to Be a Coder? includes inspiring stories from kids who are writing code now! Plus, activities, a glossary, and resources put you on the path to a fun and rewarding career with computer code today!"--